1984
DOI: 10.1524/ract.1984.35.3.173
|View full text |Cite
|
Sign up to set email alerts
|

The Removal of Cesium from Medium-Active Waste Solutions

Abstract: For the selective removal of Cs + from medium-active waste solutions, some new extraction agents were developed, based on the crown ether dibenzo-21-crown-7 combined with well-known reagents selective for Cs + . The extractive efficiency of the crown ether and of these reagents (which by themselves are not stable in MAW solutions) is synergistically enhanced on combination. The solution of the crown ether alone shows no satisfactory extraction coefficients.Among the investigated combinations of extraction agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 6 publications
(17 reference statements)
0
47
0
Order By: Relevance
“…In view of the particular challenge of achieving high selectivity for cesium ion among the alkali metal ions (2), a number of investigators have examined the extraction properties of large crown ethers (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Urgency for understanding the principles leading to cesium selectivity derives from the need for removing 131Cs from nuclear wastes (2-6,10-.…”
Section: Iniroducilonmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the particular challenge of achieving high selectivity for cesium ion among the alkali metal ions (2), a number of investigators have examined the extraction properties of large crown ethers (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Urgency for understanding the principles leading to cesium selectivity derives from the need for removing 131Cs from nuclear wastes (2-6,10-.…”
Section: Iniroducilonmentioning
confidence: 99%
“…Because of the hazard to health and environment posed by these fission products and the large cost associated with high-level nuclear waste disposal, a need has arisen to develop improved technology to separate them from these wastes (2)(3)(4)(5)(6)(10)(11)(12)15,16,18). Macrocyclic polyethers, which selectively complex alkali and alkaline earth cations, have been considered by many researchers to be promising extractants for radioactive waste treatment, Previous work in this area has indicated that the crown ethers of the 21-crown-7 (21C7) family have high selectivity for cesium cation over relatively smaller alkali metal cations such as sodium (3)(4)(5)9,10,13,14). Cesium selectivity over sodium is especially important, considering the high sodium concentration in many of the stored wastes (18 normal precision of DM was considered to be ±S% for cesium and ±10% for sodium; several sodium data points appeared to be less precise but were not excluded.…”
Section: Iniroducilonmentioning
confidence: 99%
“…Crown ethers have attracted considerable attention as Potential extractants for cesium from nuclear-waste solutions [1][2][3][4][5][6][7][8]. Among the simple crown ethers examined, alkylated derivatives of benzo-21-crown-7 and dibenzo-21-crown-7 appear most promising, either by themselves in solvents modified with fluorinated [8] or other [5,9,10] alcohols or in synergistic combination with cation exchangers [11], Selectivity ratios for cesium vs. sodium exceed 10^, though even this impressive selectivity may prove to be inadequate for treatment of high-salt wastes such as those stored at the Hanford site in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The capability of the crown ethers to bind the ionic species, make it possible to be used in many application. The crown ethers have been used in the cation extraction of radioactive waste [1][2][3], enhance selectivity in chromatography [4][5], and membrane transport [6].…”
Section: Introductionmentioning
confidence: 99%